Musculoskeletal pain management in the Emergency Department - Seremeti, Kyriaki; Vasilopoulos, George; Toylia, Georgia; Kadda, Olga; Sapountzis, Ioannis; Kourousi, Evangelia; Karimali, Dimitra; Kalogianni, Antonia; Rozis, Meletis (Health & Research Journal, 2020)
Introduction: The intensity of acute musculoskeletal pain is underestimated by health providers. Analgesia in adults that receive treatment for acute musculoskeletal pain varies from 11-29%. The timely and effective treatment of pain should become priority for the adequate pain management. Aim: The aim of the present study was to explore musculoskeletal pain management in the emergency department (ED). Material and Method: This is a descriptive study. The studied sample consisted of 82 patients, who admitted in the ED of Athen’s general hospital, due to acute musculoskeletal pain. For data collection, a special designed registration form was used. Related measurements were completed at two time points; the first time point was during patients’ admission to ED and the second one, 30 minutes post treatment or post ED discharge. Results: Patients average pain score was 7.25 ± 1.85 (first time point) and 3.76 ± 2.66 (second time point). Analgesia was provided to 51.2% of the sample and non-invasive methods were used in 51.2%. As for the frequency of the administrated drugs, analgesics were mostly preferred (29.3%), nonsteroidal anti-inflammatory drugs (NSAIDs) at 25.6% and opioids were used only at 9.8%. The mean time to first anministrated analgesic therapy was 16.56 ± 32.89 min. Conclusions: In spite of the extensive research and international guidelines for pain management, the fulfillment of the patients’ expectations for adequate and timely relief remains a challenge. The key for successful pain management lies to further education of medical stuff.